PENGARUH MODAL USAHA DAN TENAGA KERJA TERHADAP PENDAPATAN UMKM BATU BATA DI KOTA JAMBI - Ulfatun Nadhiro; Fitri Mansur; Riski Hernando (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of business capital on the income of Brick MSMEs in Jambi City, to determine the effect of labor on the income of Brick MSMEs in Jambi City, and to determine the effect of business capital and labor on the income of Brick MSMEs in Jambi City. This study is a quantitative descriptive study using primary data obtained from distributing questionnaires. The study used an analysis tool in the form of SPSS 25.0. The results of the study indicate that business capital can have a partial effect on the income of Brick MSMEs in Jambi City, labor can have a partial effect on the income of Brick MSMEs in Jambi City, and business capital and labor can have a simultaneous effect on the income of Brick MSMEs in Jambi City.